2020
DOI: 10.1111/1750-3841.15071
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of phenolic acid extract from ginseng on vascular endothelial cell injury induced by palmitate via activation of PI3K/Akt/eNOS pathway

Abstract: Elevated free fatty acids may impair insulin‐mediated signaling to eNOS that contributes to the pathophysiology of endothelial dysfunction. Previous studies have indicated the protective effect of ginseng and the regulatory potential of phenolic acid components from other plants on endothelial function. Therefore, this study investigated the protective effects of phenolic acid extract from ginseng (PG2) on endothelial cells against palmitate‐induced damage. We found that PG2 increases cell viability, inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…In addition, it was found that ginseng has the effect of suppressing kidney failure by normalizing the vascular function of kidney tissue [ 57 ]. Consistent with the above observations, ginseng extract is known to inhibit lipid accumulation in cells and promote phosphorylation of PI3K/Akt/eNOS signaling pathways through overexpression of ET-1, thereby inhibiting endothelial cell damage due to hyperlipidemia [ 58 ]. In addition, ginsenoside Rb1 normalizes calcium metabolism in vivo and in vitro vascular smooth muscle cells.…”
Section: Panax Ginseng and Ginsenosides Against Cardiac Pathogenesis Of Covid-19mentioning
confidence: 57%
“…In addition, it was found that ginseng has the effect of suppressing kidney failure by normalizing the vascular function of kidney tissue [ 57 ]. Consistent with the above observations, ginseng extract is known to inhibit lipid accumulation in cells and promote phosphorylation of PI3K/Akt/eNOS signaling pathways through overexpression of ET-1, thereby inhibiting endothelial cell damage due to hyperlipidemia [ 58 ]. In addition, ginsenoside Rb1 normalizes calcium metabolism in vivo and in vitro vascular smooth muscle cells.…”
Section: Panax Ginseng and Ginsenosides Against Cardiac Pathogenesis Of Covid-19mentioning
confidence: 57%
“…Sinapic acid increased Akt phosphorylation in a dose-dependent manner. Chen et al (2020) reported that phenolic acids extracted from ginseng protect against vascular endothelial cell injury via the activation of the PI3K/Akt/eNOS pathway [ 35 ]. Yan et al (2020) reported that gallic acid attenuated vascular dysfunction and hypertension in angiotensin II-induced C57BL/6J mice by suppressing eNOS degradation [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…F. H. Chen . These components have pharmacological effects such as cardiotonic, anti-oxidative stress, anti-myocardial ischemia, and immuno-enhancing function ( Hu et al, 2018 ; Chen et al, 2020 ). The structure can also be divided into panaxadiol, panaxatriol, and oleanolic acid types.…”
Section: Resultsmentioning
confidence: 99%